2020
DOI: 10.3390/ijms21061995
|View full text |Cite
|
Sign up to set email alerts
|

The Aggregation Conditions Define Whether EGCG is an Inhibitor or Enhancer of α-Synuclein Amyloid Fibril Formation

Abstract: The amyloid fibril formation by α -synuclein is a hallmark of various neurodegenerative disorders, most notably Parkinson’s disease. Epigallocatechin gallate (EGCG) has been reported to be an efficient inhibitor of amyloid formation by numerous proteins, among them α -synuclein. Here, we show that this applies only to a small region of the relevant parameter space, in particular to solution conditions where EGCG readily oxidizes, and we find that the oxidation product is a much more potent inhibitor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 67 publications
3
20
0
Order By: Relevance
“…However, the conditions under which these compounds are able to successfully prevent amyloid aggregation are varied. EGCG was found to inhibit insulin fibril formation at pH 7.0 but not at pH 6.0 [32], while it completely inhibits αS aggregation at pH 7.0 and actually accelerates aggregation at pH 6.0 [33]. The results of the current work show that TA is an efficient inhibitor of αS at pH 7.4 but not at pH 6.0, which is consistent with previous work in the literature utilizing similar polyphenols and IDPs [32,33].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…However, the conditions under which these compounds are able to successfully prevent amyloid aggregation are varied. EGCG was found to inhibit insulin fibril formation at pH 7.0 but not at pH 6.0 [32], while it completely inhibits αS aggregation at pH 7.0 and actually accelerates aggregation at pH 6.0 [33]. The results of the current work show that TA is an efficient inhibitor of αS at pH 7.4 but not at pH 6.0, which is consistent with previous work in the literature utilizing similar polyphenols and IDPs [32,33].…”
Section: Discussionsupporting
confidence: 91%
“…S2a, orange). This behavior is similar to previous observations of the interaction between the polyphenol EGCG and αS [32,33]. To ensure that TA does not interfere with the ability of ThT to fluoresce upon binding to amyloid fibrils and to gain a detailed picture of the aggregates formed in the presence of TA, we acquired AFM images of the endpoints of the αS control (Fig.…”
Section: Ta Becomes An Efficient Inhibitor Of As Amyloid Fibril Formation At Ph 74supporting
confidence: 80%
See 2 more Smart Citations
“…In a recent study, researchers confirmed that EGCG can accelerate α-syn amyloid fibril formation by facilitating its heterogeneous primary nucleation. This work showed that the aggregation conditions define whether EGCG is an inhibitor or enhancer of α-syn amyloid fibril formation, since the inhibitory action is not robust against various physiologically relevant changes in experimental conditions [241].…”
Section: Egcg Targeting Misfolded Aggregates In Ad and Pdmentioning
confidence: 97%